Health impact assessment in two planning projects in England: reflections on normative effectiveness - Thomas B. Fischer; Michael Chang; Tara Muthoora (BMC, 2024)
Abstract Background This article reports on research commissioned by (what was at the time) Public Health England (PHE). The objective is to reflect on the normative effectiveness of Health Impact Assessment (HIA) applied to two planning projects; (a) the new town at Cranbrook, Devon (HIA prepared in 2007), and (b) the regeneration of the Marsh farm area in Luton (HIA prepared in 2009). In this context, the focus is on the contribution of HIA to actions that are intended to lead to good or improved health and wellbeing. Methods Normative HIA effectiveness criteria derived from a literature review were used to guide the analysis. The two included HIA cases were previously identified as good practice examples with regards to procedure and report quality. Semi-structured interviews with public health, planning and other actors originally involved in the HIAs were conducted in 2021. This was followed up by web-searches for evidence on actual developments in 2023. Results Interviews indicated that normative effectiveness initially appeared to be high, but that the longer-term effects of the financial crash of 2008 reduced this. Delays in initially anticipated timelines and HIA actors moving elsewhere or retiring meant that HIAs were not followed-up and connections between developments and the HIAs were no longer made. However, web-based searches conducted in 2023 found that key HIA suggestions were eventually implemented, albeit with delay. There is also evidence for improved IMD (index of multiple deprivation) rankings in the Marsh farm regeneration case. Conclusion A mismatch is observed with regards to HIA exercises appearing to be largely 'forgotten' after over a decade of their publication, but recommendations still being implemented, possibly as a result of 'institutional memory'. Making monitoring and follow-up of HIA binding rather than advisory would allow for direct linkages to be made.